Steel, Administered Prices and Inflation: Comment - Gramm, Warren S. (Quarterly Journal of Economics, 1962)
Journal Article Steel, Administered Prices and Inflation: Comment Get access Warren S. Gramm Warren S. Gramm University of California, Davis Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 76, Issue 2, May 1962, Pages 320–325, https://doi.org/10.2307/1880825 Published: 01 May 1962